2021
DOI: 10.1177/17585732211010299
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction of pediatric lateral condyle fractures: a systematic review

Abstract: Introduction Lateral condyle fractures are the second most common pediatric elbow fracture. There exist multiple options for internal fixation including buried K-wires, unburied K-wires, and screw fixation. Our study aims to review the current literature and determine if fixation strategy affects outcomes to include fracture union, postoperative range of motion, and need subsequent surgery. Methods A systematic review of Pubmed, MEDLINE, and EMBASE databases was performed. Included articles involve pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Complications included elbow stiffness in 4.4% of the patients, nonunion in 1.4%, AVN in 1.4%, malunion in 0.8%, pin tract infections in 0.6%, and growth arrest leading to angular deformity in an additional 0.4%, and early hardware failure in 0.2%. More recently, Eckhoff et al, 27 gathered information on 1299 patients from 13 studies in a systematic review, and found a high rate of union (99.6%), and excellent or good outcomes, as determined by the Hardacre Scale, in 99% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Complications included elbow stiffness in 4.4% of the patients, nonunion in 1.4%, AVN in 1.4%, malunion in 0.8%, pin tract infections in 0.6%, and growth arrest leading to angular deformity in an additional 0.4%, and early hardware failure in 0.2%. More recently, Eckhoff et al, 27 gathered information on 1299 patients from 13 studies in a systematic review, and found a high rate of union (99.6%), and excellent or good outcomes, as determined by the Hardacre Scale, in 99% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral overgrowth can be appreciated on conventional radiographs and felt during a physical examination of the elbow [ 10 , 29 ]. The occurrence rate of this complication is comparable between both treatment groups (non-surgical, 4.5–74%; and surgical, 4.5–73.7%) and between surgical techniques (CRPP, 4.5–73.7%; ORIF K-wires, 22.1–73.7%; and ORIF cannulated screw, 10.1–74%) [ 4 , 29 , 34 , 36 , 42 , 49 , 50 , 51 ].…”
Section: Complicationsmentioning
confidence: 98%
“…The authors of each classification system for lateral humeral condyle fractures have made recommendations concerning treatment options based on the severity of the fractures; these recommendations can be found in Table 2 . In cases with a successful fracture union and without complications, the success rate for non-operative and operative lateral humeral condyle fracture, as described in meta-analyses, is between 89.8–91.5% [ 8 , 33 , 35 , 36 ]. A delayed diagnosis of these fractures (>3 weeks after injury) should initially be given based on the time between the injury and presentation and the amount of displacement, in accordance with the above-described options [ 37 , 38 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations